THE APPLICATION OF MAKE A MATCH METHOD TO IMPROVE STUDY RESULT OF ALKANES, ALKENES, AND ALKYNE - Rina Pujiastuti (Universitas Negeri Surabaya, 2018)
This classroom action researchaimed to know the application of cooperative learning type make a match can improve study result of alkanes, alkenes, and alkyne compounds class XI IA 3 SMA Negeri 1 Puncu, totaling 27 students. This study uses observation instruments and test results, held in 2 cycles. The result of this learning improvement is an increase in student learning outcomes, in the average value: pre cycle 56.3; first cycle68.9; and second cycle 85.6. The involvement of students during the learning process showed improved results, 72.8% in the first cycle to 80.8% in the second cycle. The percentage of students who scored above the KKM increased from 59% in the first cycle to 89% in the second cycle. It can conclude thatthe use of make a match method has been able to improve studyresult in material alkanes, alkenes, and alkyne.